2016
DOI: 10.1016/j.euromechflu.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Cross and magnetic helicity in the outer heliosphere from Voyager 2 observations

Abstract: Plasma velocity and magnetic field measurements from the Voyager 2 mission are used to study solar wind turbulence in the slow solar wind at two different heliocentric distances, 5 and 29 astronomical units, sufficiently far apart to provide information on the radial evolution of this turbulence. The magnetic helicity and the cross-helicity, which express the correlation between the plasma velocity and the magnetic field, are used to characterize the turbulence. Wave number spectra are computed by means of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…METHODS FOR SPECTRAL ANALYSIS Computing power spectra over a broad range of frequencies in the outer heliosphere is challenging because of the sparsity of the 48 s data (70% of magnetic field are missing). Fraternale et al (2016), Gallana et al (2016), Iovieno et al (2016) and Fraternale (2017) have demonstrated that a careful application of different, independent, techniques makes it possible to recover the spectrum with proper accuracy (e.g., with the accuracy of 10% or lower in the spectral index. The techniques description and numerical codes have been provided in the above references.…”
Section: Appendixmentioning
confidence: 99%
“…METHODS FOR SPECTRAL ANALYSIS Computing power spectra over a broad range of frequencies in the outer heliosphere is challenging because of the sparsity of the 48 s data (70% of magnetic field are missing). Fraternale et al (2016), Gallana et al (2016), Iovieno et al (2016) and Fraternale (2017) have demonstrated that a careful application of different, independent, techniques makes it possible to recover the spectrum with proper accuracy (e.g., with the accuracy of 10% or lower in the spectral index. The techniques description and numerical codes have been provided in the above references.…”
Section: Appendixmentioning
confidence: 99%
“…However, the case studies of D'Amicis & Bruno (2015) andD'Amicis et al (2016) hint that when heavy ion measurements are not available the Alfvénicity of the solar wind fluctuations may be a more reliable proxy for solar wind origin than speed. The problem with using Alfvénicity as a categorisation variable is that the solar wind becomes systematically less Alfvénic with distance (Roberts et al 1987;Bruno et al 2007;Iovieno et al 2016), due to both small scale turbulent evolution and large scale velocity shears and interaction regions (Bruno et al 2006). This means not all solar wind that started off Alfvénic near the sun is still Alfvénic when it is measured at 1 AU.…”
Section: Introductionmentioning
confidence: 99%
“…High data sparsity represents one of the major challenges to spectral analysis. A targeted breakthrough is to provide a simple and efficient way to obtain spectral information on the full frequency range contained in long, gappy temporal data sets in the many different plasma regimes sampled by the Voyager mission, see, e.g., two preliminary works by our group Fraternale et al [] and Iovieno et al []. This advancement may in the intermediate term prepare the ground for the analysis of V2 local interstellar medium plasma data and in the long term to prepare a spectral analysis standard for observational data coming from future scientific space missions inside the interstellar medium.…”
Section: Methods For Spectral Analysis Of Gapped Datamentioning
confidence: 99%